Implementation of digital competencies in higher education educational programs in Russia - G. P. Sorokina; T. A. Pershina; E. A. Dolgikh (Вестник университета)
In the context of digitalisation, the transformation of the educational process is inevitable and is a priority issue for any country that wants to maintain or improve its position on the world stage. The article presents a comparative analysis of digital competencies and the possibility of their implementation in the higher education system in Russia. The comparison of the formulated competencies in the methodology approved by the Order of the Ministry of Economic Development of the Russian Federation No. 41 dated January 24, 2020, as well as the International Telecommunication Union and other European organisations is considered. The descriptors (knowledge, skills and abilities) of graduates in various fields who, in the era of digitalisation, must have the necessary digital competencies are identified. Today, professional standards, even in the humanities, define the requirements for technical and computer skills. The article proposes formulations of universal competencies in the higher education system based on the analysis.